Booking Service Application on Jhon Motor Android Based - Muhamad Iqbal; Mesterjon Mesterjon; Yode Arliando (Jurnal Komputer, Informasi dan Teknologi, 2021)
Jhon Motor is a workshop engaged in the sale of spare parts and also service. So far, the service system at Jhon Motor is still done manually, by means of consumers coming directly to the service area or calling Customer Service to set a booking service schedule. However, the problem that often occurs is when the service schedule is full or full, consumers who come directly cannot do service on the same day because they have to reschedule for service. In addition, there are some consumers who cannot contact Customer Service, because of the many incoming calls to make a booking service. The Booking Service application at Jhon Motor is made using the PHP and Java programming languages, with a MySQL database. The software used for making the application is Adobe Dreamweaver CC 2019, Android Studio, and XAMPP. The Booking Service application at Jhon Motor is a medium or container that can be used to assist the booking service process at Jhon Motor, which is still done conventionally. The Booking Service application at Jhon Motor has 2 interfaces, namely web-based (accessed by the Jhon Motor administrator) and Android-based (accessed by consumers who want to book service). The Booking Service application at Jhon Motor also has 1 (one) database server, so that whatever is processed in a web-based application, the information on the Android application automatically changes. Based on the results of tests carried out both offline and online, web-based applications can process data properly and smoothly, and Android-based applications successfully display service fee information and can make booking services.